2022
DOI: 10.12804/revistas.urosario.edu.co/empresa/a.11133
|View full text |Cite
|
Sign up to set email alerts
|

Medición del valor de marca basado en las percepciones del turista internacional: una investigación sobre Villavicencio (Colombia)

Abstract: Este estudio examina el valor de marca de Villavicencio como destino turístico internacional desde el punto de vista del consumidor. Además, analiza la influencia del social media durante el Covid-19 en las intenciones de repetir la visita al destino. Se realizó un estudio cuantitativo, en el que se procesaron 130 encuestas aplicadas a turistas de diferentes países. Los resultados indican que la lealtad y la calidad percibida del destino son las dimensiones que más aportan a la construcción del valor de marca.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As indicated in Table 1 , the majority of the articles reported that their survey participants were domestic tourists, which is not surprising due to travel restrictions and border closures during 2020. Indeed, most studies that used samples of international tourist respondents collected their survey data later in 2021 (e.g., Otero-Gomez and Giraldo-Perez, 2022 ; Šerić and Mikulić, 2022 ; Carvache-Franco et al, 2022a , b ). Of the reviewed studies, 7 utilized co-variance based structural equation modeling (CB-SEM), while 11 employed partial least squares structural equation modeling (PLS-SEM), in line with the growing popularity of PLS-SEM in tourism marketing research ( Hair et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As indicated in Table 1 , the majority of the articles reported that their survey participants were domestic tourists, which is not surprising due to travel restrictions and border closures during 2020. Indeed, most studies that used samples of international tourist respondents collected their survey data later in 2021 (e.g., Otero-Gomez and Giraldo-Perez, 2022 ; Šerić and Mikulić, 2022 ; Carvache-Franco et al, 2022a , b ). Of the reviewed studies, 7 utilized co-variance based structural equation modeling (CB-SEM), while 11 employed partial least squares structural equation modeling (PLS-SEM), in line with the growing popularity of PLS-SEM in tourism marketing research ( Hair et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three journals published more than one of the works reviewed: Sustainability (five articles), Journal of Destination Marketing & Management (three articles), and Current Issues in Tourism (two articles). The fact that two studies were published in Spanish language journals by Otero-Gomez and Giraldo-Perez (2022) in Revista Universidad & Empresa , and by Garcia-Reinoso et al (2021) in El Periplo Sustentable reflects the growing interest of academics based in Latin America to disseminate their research to broader audiences through journals indexed in international databases ( Cruz-Milán, 2014 ). The review identified recurrent theories and conceptual frameworks under which the hypotheses were developed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations